Three-dimensional ultraflexible triboelectric nanogenerator made by 3D printing. (March 2018) - Chen, Baodong; Tang, Wei; Jiang, Tao; Zhu, Laipan; Chen, Xiangyu; He, Chuan; Xu, Liang; Guo, Hengyu; Lin, Pei; Li, Ding; Shao, Jiajia; Wang, Zhong Lin
Abstract: As the fast developments of wearable devices, artificial intelligences and Internet of Things, it is important to explore revolutionary approach and fabrication method for providing flexible and sustainable power sources. We report here a practical, ultraflexible and three-dimensional TENG (3D–TENG) that is capable of driving conventional electronics by harvesting biomechanical energy. Such TENG is made for the first time by the unique additive manufacturing technology—hybrid UV 3D printing. The TENG is made up of printed composite resin parts and ionic hydrogel as the electrification layer and electrode. A sustainable and decent output of 10.98 W/m 3 ( P v, peak power per unit volume) and 0.65 mC/m 3 ( ρ sc, transferred charge per unit volume) are produced under a low triggering frequency of 1.3 Hz, which is attributed to the Maxwell's displacement current. Meanwhile, a self-powered SOS flickering and buzzing distress signal system, and smart lighting shoes are successfully demonstrated, as well as self-powered portable systems of a temperature sensor or a smart watch. Our work provides new opportunities for constructing multifunctional self-powered systems toward the applications in realistic environments. Graphical abstract: A practical, ultraflexible and three-dimensional triboelectric nanogenerator (3D–TENG) is fabricated by hybrid 3D printing. The ultraflexible 3D-TENG can be easily applied for biomechanical energy harvesting under low frequency human motions. The self-powered wearable devices such as LEDs flickering and buzzing SOS distress systems, and smart LEDs lighting shoes are successfully demonstrated. Especially, an ultraflexible self-powered source which provides enough power for driving and charging common electronics, is also successfully developed (such as, a temperature sensor and a smart watch).fx1 Highlights: A practical, ultraflexible 3D–TENG was made by hybrid 3D printing. The device can be easily applied for biomechanical energy harvesting. Self-powered wearable devices are successfully demonstrated. Especially, as ultraflexible self-powered source is also successfully developed.